2003
DOI: 10.1037/0022-0167.50.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Perceived coping as a mediator between attachment and psychological distress: A structural equation modeling approach.

Abstract: This study examined perceived coping (perceived problem-solving ability and progress in coping with problems) as a mediator between adult attachment (anxiety and avoidance) and psychological distress (depression, hopelessness, anxiety, anger, and interpersonal problems). Survey data from 515 undergraduate students were analyzed using structural equation modeling. Results indicated that perceived coping fully mediated the relationship between attachment anxiety and psychological distress and partially mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
159
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 54 publications
(91 reference statements)
21
159
3
6
Order By: Relevance
“…In other words, persons with a high level of attachment anxiety and/or attachment avoidance tend to use ineffective coping strategies, which, in turn, increase their level of depression. Wei et al (2003) examined this pattern and found that ineffective coping served as a mediator between attachment and distress for a sample of college students. However, because these analyses were based on concurrent measures, it is not possible to draw any firm conclusions about the causal relations among these variables.…”
Section: Attachment Ineffective Coping and Depressionmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, persons with a high level of attachment anxiety and/or attachment avoidance tend to use ineffective coping strategies, which, in turn, increase their level of depression. Wei et al (2003) examined this pattern and found that ineffective coping served as a mediator between attachment and distress for a sample of college students. However, because these analyses were based on concurrent measures, it is not possible to draw any firm conclusions about the causal relations among these variables.…”
Section: Attachment Ineffective Coping and Depressionmentioning
confidence: 99%
“…Research has indicated that, in college student samples, ineffective coping serves as a mediator between attachment and distress (Lopez et al, 2001Wei et al, 2003), maladaptive perfectionism serves as a mediator between attachment and depression (Wei et al, 2004), and avoidant coping (an index of ineffective coping) serves as a mediator between maladaptive perfectionism and depression (Dunkley et al, 2000(Dunkley et al, , 2003. On the basis of the results of these studies, it seems possible that the quality of attachment may contribute to the development of maladaptive perfectionism, ineffective coping, and depression among college students (i.e., attachment anxiety or avoidance3 maladaptive perfectionism 3 ineffective coping 3 depression).…”
Section: Current Studymentioning
confidence: 99%
See 3 more Smart Citations